Why are there so many power laws in economics? - Jakob Kapeller; Stefan Steinerberger (University of Duisburg-Essen, Institute for Socio-Economics (ifso), 2025)
Power law distributions are ubiquitous in socioeconomic contexts. While their general properties are well understood, it is often less clear why they regularly appear in empirical data. What are the generative mechanisms leading to power laws, how do they arise in the real world? This paper aims to partly fill this gap by discussing two candidate mechanisms that appear especially relevant for understanding the emergence of power laws in socioeconomic contexts. We identify core formal properties and potential real-world equivalents of these mechanisms. In addition, we explore the relation of power laws to indirectly related concepts relevant in heterodox economics, like path dependence, cumulative effects, power asymmetries or non-ergodicity.
Keywords: B52; D00; D30; 330; power law distributions; inequality; generative mechanisms; wealth inequality; firm size